Comparative study of molecular mechanism of action of allopathic drugs and herbal drugs: A mini review - Singh, Pramod Kumar; Gautam, Ajay Kumar; Puranik, Nidhi; Rai , Dr.Bijendra; Yadav, Dhananjay (Progress in Nutrition, 2023)
Different kinds of allopathic medications are already accessible that operate admirably in managing sugar levels through their distinct action mechanisms; nonetheless, the point of worry is that they cause our body organs to overwork or, in other words, they overstress our bodies. Quite a few allopathic medicines are known to cause adverse reactions. None of these however provide a cure for diabetes, although they do assist in successful diabetic control. Polyherbal formulations are a concept unique to Ayurveda. Natural compounds commonly known as phytochemicals originating from plants have played a significant part in medication development efforts and still do. Given the toxicity and myriad negative consequences of allopathic medications, it is possible to greatly expand the number of herbal drug manufacturing enterprises, which is related to the current growth in interest and demand for herbal medicines. Additionally, plant-based phytochemical medications offer a plentiful supply of physiologically active substances with pharmacological action and little side effects. Since various preparations function by distinct mechanisms, theoretically alternative combinations of these extracts may be more successful in lowering blood glucose levels. In this study, we sought to elucidate the mechanism of plant phytochemical anti-diabetic properties in polyherbal formulations.